Dysfunkcjonalność szwajcarskiego systemu demokracji bezpośredniej na przykładzie procesu integracji mniejszości muzułmańskiej - Matyja, Mirosław (Studia Politicae Universitatis Silesiensis, 2017)
Abstract: Dysfunctionality of the Swiss system of direct democracy on the example of the integration of the Muslim minority Analysing the role of the Muslim minority in Switzerland is important to specify the role of Swiss direct democracy, which determines the status of religious minorities in this country. The Swiss political system is blocking the rights of Muslim religious minority and its full integration in Switzerland and in the Swiss society. In Switzerland exists the negative impact of direct democracy on the integration of Muslim religious minority. Limitation of full rights for the minority confirms the phenomenon of dysfunctionality in the Swiss direct democracy system. The analysis of this unexplored or wrongly interpreted problem is the subject of this article. Key words: system of direct democracy, disfunctionality, Musslim minority